A Study of 28 Pediatric Patients With Drug Crystals Following Tosufloxacin Administration - Toshihiko Mori; Mayu Hachiya; Hikaru Takahashi; Yukiko Higashide; Jun Kunizaki; Emiko Hoshino; Nodoka Sakurai; Nami Tosaoka; Yasunari Takakuwa; Azusa Kawaguchi; Kenji Kondo (Infectious Diseases in Clinical Practice, 2026)
Background: Tosufloxacin (TFLX) is an oral fluoroquinolone antibiotic that has been reported to cause crystalluria and acute kidney injury. To clarify the clinical course of drug crystals after TFLX administration in children, we conducted a retrospective review of pediatric patients who developed drug crystals after receiving TFLX. Methods: This retrospective study included 28 pediatric patients aged 15 years or younger who were treated in the Department of Pediatrics at NTT Medical Center Sapporo, Japan, between January 1, 2016, and March 31, 2026, and in whom drug crystals were detected in urine sediment after TFLX administration. Results: The median age of the patients at diagnosis was 6.5 years (interquartile range: 4.4 to 8.2 y), and 11 patients (39%) were male. The median time to diagnosis after TFLX administration was 2 days (interquartile range: 1 to 3 d). Gastrointestinal symptoms, such as vomiting and abdominal pain, were observed in 6 patients (21%), and decreased appetite was observed in 3 patients (11%). All patients who had a known dosage received an appropriate dose of TFLX. Ten patients (36%) were diagnosed with acute kidney injury, and they improved within 3 to 5 days after discontinuing TFLX and replacing fluids. Conclusions: Despite the administration of the appropriate TFLX dosage, drug crystals were observed in the urine sediment 1 to 4 days after administration. When administering TFLX, it is important to be aware that drug crystals and acute kidney injury may occur. Discontinuing the drug can prevent progression of kidney injury.